Pengaruh Harga Kamar, Fasilitas, Dan Kualitas Pelayanan Terhadap Kepuasan Tamu Menginap Pada Hotel Labersa Di Kabupaten Toba - Booni Tauhid; Robert Deffie; Handoko (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2022)
Guests who come and visit need interesting tourist attractions in an area will need good accommodation facilities. a very promising business field because the public, guests and state apparatus who go to an area for work or entertainment are in dire need of lodging or hotel services. The approach and type of research is based on a quantitative approach with descriptive research type. The sampling is purposive sampling with a sample of 100 hotel guest respondents staying at the Labersa Balige Hotel. The results show that room rates and facilities have a significant impact on positive and significant effect on guest satisfaction. Service quality has a negative and insignificant effect on guest satisfaction at Hotel Labersa. Based on F test results that facilities, room prices and service quality simultaneously affect guest satisfaction at Hotel Labersa., service quality, guest satisfaction at Hotel Labersa. The results showed that simultaneously from the results of the F test 96.31% of the facilities, room prices, and services had a positive and significant impact on guest satisfaction Staying. Service quality has a negative and insignificant effect on guest satisfaction at Hotel Labersa. Based on the results of the t-test -0.703 with a significant level of 0.484 that the quality of service partially has a negative effect on guest satisfaction staying at Hotel Labersa.